ANALISA TRANSFER MASSA DISERTAI REAKSI KIMIA PADA ABSORPSI CO2 - Kusnaryo, Radya Purna Wijaya, Ali Altway, (Jurnal Teknik Kimia, 2008)
The aim of this research is to study mass transfer in CO2 absorptions a packed column for nonisothermal reversible reactions. The study was developed experimental and simulation co2 with air andpotassium carbonate solution is the matter used in this research.The arrangement counter current packed column to which a CO2 – air mixture flow is feed from the bottomand potassium carbon from the top of column.The work of simulation developed with microscopic mass and energy balance in column.The effect of flow absorbent and K2CO3 concentration is study do to percent CO2 removal. The results is;in range flow 3-5 l/mm have 10 % diviasi and range flow : 5-7 l/mnt was have deviasi in range 10-30 %Key words :mass transfer, absorption, non-isothermal, packed column